Approximating and computing behavioural distances in probabilistic transition systems - van Breugel, F; Worrell, J (2006)
In an earlier paper we presented a pseudometric on the states of a probabilistic transition system, yielding a quantitative notion of behavioural equivalence. The behavioural pseudometric was defined via the terminal coalgebra of a functor based on a metric on Borel probability measures. In the present paper we give a polynomial-time algorithm, based on linear programming, to calculate the distances between states up to a prescribed degree of accuracy. © 2006 Elsevier B.V. All rights reserved.